Uji Daya Antioksidan Ekstrak Air Biji Kedelai Kuning (Glycine max (L) Merill) Dibandingkan Vitamin E pada Tikus Putih (Rattus norvegicus) Jantan yang Diinduksi CCI4 - Yuliana, Eka; miladiyah, isnatin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
The production of free radiacals (oxidants) that are not in balance with antioxidant activity can cause cell damage. The need for antioxidant is absolutely necessary not only endogenous but also exogenous. Yellow soybean is one ofthe plants that have antioxidant activity, which can reduce the effects of free radicals while vitamin E is a powerful antioxidant which is used. This study aims to determine antioxidant activity of water extract in the soybean seed yellow (Glycine max (L) Merill) compared the decreased content of vitamin E on malondialdehyde (MDA) in the rat (Rattus norvegicus) male induced by CCL4. This study is an experimental research laboratory with a pretest-posttest control group. 25 male rats (Rattus norvegicus) were divided into 5 treatment groups. Group I (positive control vitamin E), group II, III, and IV were given water extract of yellow soybean (Glycine max (L) Merill) with a concentration of 2.5%, respectively, 10%, and 40%. Group Vis a negative control distilled water. Treatment was given for 5 days. On 6th day, all groups treated with CCL4 0.2 ml/200 g 88. Antioxidant activity measured by the decrease in serum MDA levels before and after treatment. Statistical analysis using One Way ANOVA. In One Way Anova test p value = 0.196 (p> 0.05), which showed no significant difference (not significant) toward the mean decrease in rat blood serum MDA in all groups Water extract of yellow soybean (Glycine max (L) Merill) a difference between the antioxidant actiVity compared vitamm E as an antioxidant in white rats (Rattus novergicus) male Wistar strain which has been induced CCL4 but this difference was not statistically significantly.